Wolf-Hirschhorn Syndrome: Clinical and Genetic Study of 7 New Cases, and Mini Review - Eva-Cristiana Gavril; Alina Costina Luca; Alexandrina-Stefania Curpan; Roxana Popescu; Irina Resmerita; Monica Cristina Panzaru; Lacramioara Ionela Butnariu; Eusebiu Vlad Gorduza; Mihaela Gramescu; Cristina Rusu (MDPI AG, 2021)
Wolf-Hirschhorn syndrome (WHS), a rare disorder determined by distal 4p deletion, is characterized by a pre and postnatal growth retardation, hypotonia, intellectual disability, epilepsy, craniofacial dysmorphism, and congenital fusion anomalies. The clinical aspects are dependent on the deletion' size. Our aim was to identify rare specific characteristics in a cohort of seven cases with 4p deletion and to assess the utility of Multiplex ligation-dependent probe amplification (MLPA) (cheap and sensitive test)-combined kits-as a diagnostic test and selection tool for cases that require other investigations (chromosomal microarray analysis-CMA, karyotype). For all cases we conducted a clinical examination with the main features identified: facial dysmorphism, intellectual disability, postnatal development delay, cardiac defects and hypotonia. In some cases, we observed seizures, structural brain abnormalities, immunodeficiencies, and renal anomalies. Prenatal growth retardation was detected in a relatively small number of cases, but postnatal growth failure was a constant feature. In all cases, the clinical diagnosis was confirmed by genetic analyses: karyotype and/or MLPA. In conclusion, renal and brain defects, as well as immunodeficiency are rare manifestations and should be looked for. Although CMA is the standard test, in our experience, MLPA is also a reliable screening method as the identified cases were either confirmed by MLPA or selected for further investigations.